Material modifications enhancing the antibacterial properties of two biodegradable poly(3-hydroxybutyrate) implants. (23rd December 2020) - Ferlic, P W; Nogler, M; Weinberg, A M; Kühn, K D; Liebensteiner, M; Coraça-Huber, D C
Abstract: The aim of this study was to evaluate the antimicrobial efficacy of adding a gentamicin palmitate (GP) coating and zirconium dioxide (ZrO2 ) to biodegradable poly(3-hydroxybutyrate) (PHB) to reduce biofilm formation. Cylindrical pins with and without a coating were incubated in Müller-Hinton broth inoculated with 2 × 10 5 colony-forming units (CFU) ml-1 of Staphylococcus aureus for 2 d or 7 d, then sonicated to disrupt biofilms. Pure PHB (PHB + GP) and PHB pins with ZrO2 added (PHBzr + GP) were coated with GP and compared with PHB pins lacking a coating (PHB). Cells (CFU) were counted to quantify the number of bacteria in the biofilm and a cell proliferation assay was employed to evaluate metabolic activity, and scanning electron microscopy (SEM) was performed to visualize the structure of the biofilm. After 2 d of incubation there were significantly more cells in biofilms on PHB pins than PHB + GP and PHBzr + GP pins ( p < 0.0001), and cells in the sonication fluid obtained from GP-coated pins exhibited significantly lower metabolic activity than cells from uncoated PHB pins ( p < 0.0001). After 7 d of incubation metabolic activity was lowest for PHBzr + GP, with significant differences between PHB and PHBzr + GP ( p = 0.001). SEM revealed more cells attached to the surface, and more structured biofilms, on pins without a coating. Coating pins with GP significantly reduced early biofilm formation on PHB implants. This could lower the potential risk of surgical site infections when using PHB implants. Addition of ZrO2 might further enhance the antibacterial properties. Such modification of the implant material should therefore be considered when developing new biodegradable PHB implants.